Stable enclosure based hybrid routing schema in heterogeneous wireless networks - Zhi LI; Yi JIANG; Qian-mu LI; Feng-yu LIU (Tongxin xuebao)
The model of heterogeneous wireless networks was analyzed and a hybrid routing schema based on MANET stable enclosure was proposed.This schema could transform the routing protocol between MANET and DTN based on the local topology in real time.In the stable enclosure,AODV was used to improve packet relaying efficiency.When packet relayed to the disconnected area,the routing protocol transcended to Prophet to avoid routing failed.It fully used the advantage of MANET and DTN routing protocol.The feasibility of the proposed algorithm is demonstrated,and it is more efficient than the other DTN routing protocols used in the heterogeneous wireless networks.